Удосконалення технології виробництва гірких настоянок за допомогою математико-статистичних методів досліджень - Попова, Наталія Вікторівна; Мисюра, Тарас Григорович; Рибачок, Альбіна Вікторівна (My University, 2016)
В статті представлено новий спосіб виробництва гірких настоянок, який полягає в екстрагуванні водою пряно-ароматичної сировини з подальшим концентруванням екстрактів та купажуванні з водно-спиртовою сумішшю. Режими виробництва уточнювалися за допомогою експериментально-статистичних методів математичного моделювання. Було підібрано оптимальні режими проведення процесу екстрагування сировини для отримання основних складових настоянки та забезпечення її високої якості. При цьому готова настоянка проявлятиме загальнозміцнюючий ефект на організм людини та матиме короткі терміни виробництва. Improvement of technology of production of bitter tinctures, which will provide short spaces of production, also bitter tinctures will show the high biological value of drink and a positive effect on the human organism. Design. Methodology. Approach. By a basic instrument improvements in this work is mathematic-statistical methods of researches and program STATISTICA 6.0ru. Essence of method of production of bitter is tinctures consists in the following. At first dry powders spicily aromatic raw material does release from different admixtures and separately extract water at permanent interfusion and temperature 40ºC with subsequent filtration and concentration to the set maintenance of dry matters. The next technological stage is mix of extracts with an alcohol to durability 40% at. The eventual stage of production is mix of extracts and solution of honey. For a receipt and analysis of experimental data, the multivariable experiment of type was planned 22 and 3n and the used methods of determination of vitamin C and phenolic compounds. For processing of experimental data used experimentally statistical methods of mathematical design. Conclusions. Thus, made the optimum values of correlation and duration of process of extracting accordingly for to the cardamom 14,5 and 83 minutes; for a ginger – 13 and 70 minutes ; for a pepper bitter 17 and 92 minutes.
Keywords: гіркі настоянки; процес екстрагування; гідромодуль; тривалість; вітамін С; фенольні сполуки; математико-статистичні методи дослідження; mathematic-statistical research methods; bitter tinctures; process of extracting; correlation; duration; vitamin C; phenolic compounds; кафедра процесів і апаратів харчових виробництв; кафедра експертизи харчових продуктів